PENGEMBANGAN KOMPETENSI PROFESIONALISME GURU DALAM MENGHADAPI PROBLEMATIKA DI ERA DIGITAL - Abdurahmansyah, Hafiz Alfansyah, Rita Novita Sari, Dewi Tiara Sari, Nurul Afifah, (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education is a conscious and planned effort to improve the quality of human resources so that we can compete in the future. Education is a long-term investment and is the key to a better future in the life of our nation and nation. Education is the most important process in the country. It is necessary to take strategic steps to build teacher professionalism competence. The purpose of this article is to see the extent to which the development of teachers' personalism competencies in dealing with problems in the digital era This change emphasizes the need for teachers to have skills that are in accordance with the learning needs of the digital era. The research methods used are descriptive qualitative methods and literature study methods. It is hoped that the results of this study will provide a deeper understanding of the importance of improving teachers' professional skills, which include pedagogical, personality, social, and professional aspects.